Deconstructing Paon: Spatial of Meaning within the Balinese Domestic Realm of Penglipuran Village - Cliff Hakim; Widad Raditya; Divta Wedanta; Lintu Tulistyantoro (Jurnal Koridor, 2026)
In Balinese culture, the domestic environment embodies cosmological, social, and gendered meanings rooted in the philosophy of Asta Kosala Kosali. Within this system, the paon or Balinese traditional kitchen is not merely a utilitarian zone but a symbolic domain where fire, femininity, and sustenance converge. Despite its rich historical and cultural significance, the paon has rarely been examined in architectural discourse, often overshadowed by studies of Bali’s temples and sacred compounds. This lack of scholarly attention limits understanding of how everyday domestic spaces express cosmology and social hierarchy. Addressing this gap, this study investigates the paon in Penglipuran Village, one of Bali’s most intact traditional settlements, as a key site of spatial meaning and ritual continuity. Using Henri Lefebvre’s theory of the production of space alongside Asta Kosala Kosali, this qualitative descriptive research applies ethnographic observation and interviews with local residents. The findings reveal the paon as a socially produced space where physical form, spiritual symbolism, and daily practice interweave, reflecting the balance between sacred and profane realms. The study contributes a new perspective that connects global spatial theory with Balinese cosmology, advancing discourse on domestic sacredness and gendered spatial production in vernacular architecture.